Rorak Efectivity for Soil Conservation on Coffee Plantations - Asrizal; Dharmawati, Nuraeni Dwi; Purwoto, Harsunu (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
This study was conducted to analyze land differences with Roraktreatment and without Rorakon the physical and chemical properties of the soil. The analysis used is quantitative descriptive by processing primary data (physical and chemical properties of soil) and secondary data (data from the study of literature and climate data in the researcharea). The results showed differences in the physical properties of the soil in each treatment. The specific soil gravity without a Rorakwas higher (1,26 g/cm3) than the Roraktreatment (1.24 g/cm3). The weight of the soil volume in the treatment withoutrorak was higher (0.89 g/cm3) than in the Roraktreatment (0.55 g/cm3). The porosity in the rorak treatment was higher (55.5%) than without the Rorak(29.5%). The maximum moisture content of the Roraktreatment was 82.54% higher than without rorak 68,35%.The results showed the chemical properties of the soil showed that there were differences in the chemical properties of each treatment. Soil chemical properties in Roraktreatment had higher levels of Nitrogen (0.50%), Phosphorus (7.33 ppm), Potassium (0.42 me/100 g), and C-organic (4.1 %) than treatment without RorakNitrogen (0.16 %), Phosphor (7.18 ppm), Potassium (0.24 me/100 g), C-Organic (2.3%). Making a Rorakwith a length of 1.50 m, a width of 1.00 m in 0.40 m, the capacity of which is 0.60 m3, thewater in the rorak will run out in an average of 1.96 hours with an average water infiltration rate 0.32 m3/hour. The optimal amount of Rorak/ha is 336 because it has an available water volume of 201.60 m3/ha/day. This amount can meet the water needs of coffee plants, which is 180 m3/ha/day.